SECONDARY PACKAGING SELECTION FOR CUBE CHILI WITH AHP METHOD, CONSUMER PREFERENCE LEVEL AND VALUE ADDED - Febri Boyanda Sinaga; Kurnia Herlina Dewi; Evanila Silvia (BPFP Faperta UNIB, 2012)
Cube chili has potential to be commercialized. However, packaging of the product has not yet been prepared well for commercialized purpose. Therefore, it’s necessary to do a research about product packaging. This research aims to obtain the best secondary packaging for cube chili, determine the level of consumer preference towards the packaging and get the information about the added value of packaged cube chilli. Selection of the best secondary packaging for cube chili according assessment from 5 experts with Analytical Hierarchy Process (AHP) method, distributing hedonic test questionnaires to 25 customers for the selection of the preferred packaging, analyzed with Kruskal Wallis method and determination of the added value packaging with Hayami method. Secondary packagings that have been used are plastic box polistirene (PS) with thickness of 0.167 mm, folding box carton (FC) with thickness of 0.5 mm and plastic box polistirene (PS) with thickness of 1 mm. Result of this research showed that the best secondary packaging according to expert assessment is PS box 1 mm (0,468). The packaging of cube chili that most preferred by consumers is FC-box 0.5 mm (4,44). The highest added value is owned by the cube chili that packed with PS boxes 0.167 mm (51.89%)